The Impact of Nutritional Marketing Claims on Consumer Behavior and Food Choices Based on Medical Ethics - Mahendra Wisnu W, I K Rama; Basrowi, Ray Wagiu (Ridwan Institute, 2024)
The impact of claims made by nutrition marketing has a major influence in shaping consumer behavior and influencing food choices, but there is a fairly complex ethical side that needs special attention. Claims that are often marketed are related to solutions to health problems, but often simplify information or manipulate consumer perceptions. This will lead to unrealistic expectations and misinformation. Ethical issues also arise in vulnerable groups, such as the elderly, people with disabilities, or groups with minimal access to literacy. This group will be most affected, because the accumulation of misinformation will be seen in old age, such as health problems. The emergence of unrest regarding claims made by the marketing department has raised concerns about which priority is profit or public health. It is important for policymakers to balance commercial profit with health and of course integrity and transparency to prevent misinformation. We used a systematic review procedure, the literature was reviewed to examine the impact of nutrition marketing claims on consumer behavior and food choices based on medical ethics. We selected journals in the last 10 years through the PubMed, Elsevier, ProQuest, and Google Scholar databases with keywords: nutrition, health, marketing. Journals that do not meet the keywords will be excluded from the review. The study has shown that, while nutrition claims may encourage some consumers to increase their nutritional knowledge and choose healthier options, they may also encourage consumers to increase their overall food consumption and energy intake. The study has shown that, while nutrition claims may encourage some consumers to increase their nutritional knowledge and choose healthier options, they may also encourage consumers to increase their overall food consumption and energy intake. This has the potential to undermine efforts to address health issues such as overweight and obesity. This study explores the factors that influence shopper attitudes, by examining the impact of demographic, socio-cultural and individual attitudes on health claims made through nutrition marketing.